2003
DOI: 10.1103/physrevb.68.094401
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale origin of the magnetocaloric effect in Ni-Mn-Ga shape-memory alloys

Abstract: We have analyzed magnetization measurements in a series of composition-related Ni-Mn-Ga shape-memory alloys. It is shown that the magnetocaloric effect in the vicinity of the martensitic transition mainly originates from two different contributions: ͑i͒ magnetostructural coupling on the mesoscopic scale between the magnetic moments and the martensitic variants, which is also responsible for the magnetic shape-memory effect and ͑ii͒ the microscopic spin-phonon coupling which gives rise to the shift of the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(86 citation statements)
references
References 22 publications
4
82
0
Order By: Relevance
“…[11,12] For example, varying x from 0 to 0.2 causes T C to decrease from 376 to 325 K and T M to increase from 210 to 325 K. Giant-magnetocaloric effect has been observed in samples where T C and T M are equal. [8,13] In this paper, we report 5% negative magnetoresistance (MR) at 8 T in bulk Ni 2+x Mn 1−x Ga polycrystals at room temperature. To the best of our knowledge, there are no MR studies in literature till date on well characterized bulk Ni 2+x Mn 1−x Ga samples as functions of composition and temperature.…”
mentioning
confidence: 99%
“…[11,12] For example, varying x from 0 to 0.2 causes T C to decrease from 376 to 325 K and T M to increase from 210 to 325 K. Giant-magnetocaloric effect has been observed in samples where T C and T M are equal. [8,13] In this paper, we report 5% negative magnetoresistance (MR) at 8 T in bulk Ni 2+x Mn 1−x Ga polycrystals at room temperature. To the best of our knowledge, there are no MR studies in literature till date on well characterized bulk Ni 2+x Mn 1−x Ga samples as functions of composition and temperature.…”
mentioning
confidence: 99%
“…It has been demonstrated that the MCE effect strongly depends on the nature of magnetic transitions in the magnetic materials. A number of compounds such as Ga 5 Si 2 Ge 2 [1], LaFe 13−x Si x [2,3], MnAs 1−x Sb x [4] and MnFeP 1−x As x [5], Ni-Mn-Ga [6][7][8][9][10][11], exhibit a large MCE because of the first-order nature of their magnetic transition. Among those materials, an attractive candidate is the Mn-based Heusler alloys.…”
mentioning
confidence: 99%
“…The most striking features of the ΔS M are the large and positive entropy change within the MT temperature range. The positive sign of ΔS M exists even under high magnetic field, showing the mechanism involved is different from that of Co-free Ni-Mn-Ga alloys which is related to the coupling between the martensitic and magnetic domains [4]. The modification of magnetic order through magnetic-field-induced reverse MT from partially AFM martensite to FM austenite is responsible for the IMCE in the present alloy.…”
Section: Resultsmentioning
confidence: 77%
“…The maximum MCE was obtained when structural and magnetic transition temperatures overlap each other (T M = T c ) [3]. Furthermore, an extrinsic inverse MCE (IMCE, namely, positive ΔS M ) phenomenon has also been reported in several Ni-Mn-Ga alloys under application of low magnetic field, arising from the coupling between the martensitic and magnetic domains at the mesoscale [4], i.e., magnetization change due to martensite reorientation associated with the high magnetic anisotropy. However, this process cannot result in a true ΔS M since it is originated from the field dependent change of magnetic order parameter [7].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation